Financial Factor Analysis of the Performance of Transportation and Logistics Companies on the IDX (2019-2023) - Fiska Amelita; Denny Kurnia (International Forum of Researchers and Lecturers, 2025)
This study aims to investigate the effects of liquidity, financial leverage, capital structure, and operating cash flow on financial performance, with financial distress serving as a mediating variable. The population comprises transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, totaling 37 companies. The sample includes 20 companies, with quarterly financial reports yielding 400 observations. Secondary data were employed, and purposive sampling was utilized for sample selection. The analysis was conducted using panel data analysis at a 5% significance level, facilitated by STATA Version 17 software. Mediation was tested utilizing the Sobel test with a critical value of 1.96. The results reveal that liquidity significantly impacts both financial distress and financial performance; financial leverage significantly affects both financial distress and financial performance; capital structure significantly influences financial distress but does not significantly affect financial performance; operating cash flow does not significantly impact financial distress but significantly affects financial performance. Collectively, liquidity, financial leverage, capital structure, and operating cash flow significantly influence financial distress. Furthermore, liquidity, financial leverage, capital structure, operating cash flow, and financial distress together have a significant effect on financial performance. Mediation analysis indicates that financial distress significantly mediates the relationships between liquidity, financial leverage, capital structure, and financial performance, whereas financial distress does not significantly mediate the effect of operating cash flow on financial performance. It is recommended that transportation and logistics companies listed on the IDX actively enhance liquidity, optimally manage leverage and capital structure, and strengthen operational cash flow management to minimize financial distress risk and sustain financial performance.